2016
DOI: 10.3390/ijms17091386
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of a Novel Compound CW-33 against Japanese Encephalitis Virus through Inhibiting Intracellular Calcium Overload

Abstract: Japanese encephalitis virus (JEV), a mosquito-borne flavivirus, has five genotypes (I, II, III, IV, and V). JEV genotype I circulates widely in some Asian countries. However, current JEV vaccines based on genotype III strains show low neutralizing capacities against genotype I variants. In addition, JE has no specific treatment, except a few supportive treatments. Compound CW-33, an intermediate synthesized derivative of furoquinolines, was investigated for its antiviral activities against JEV in this study. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…CW-33A significantly inhibited the late stage of JEV replication in vitro , including intracellular virus production, viral protein expression and viral genome synthesis (Figs 7 – 10 ). The result indicated antiviral mechanism of CW-33A was consistent with that of CW-33 reported in a prior study that CW-33 declined the late stage of JEV replication via antagonizing the suppression of ERK1/2, Akt/mTOR, and Jak/STAT pathways by JEV 9 . CW-33A might have a clinical application on interfere post-entry stages during JEV replication.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…CW-33A significantly inhibited the late stage of JEV replication in vitro , including intracellular virus production, viral protein expression and viral genome synthesis (Figs 7 – 10 ). The result indicated antiviral mechanism of CW-33A was consistent with that of CW-33 reported in a prior study that CW-33 declined the late stage of JEV replication via antagonizing the suppression of ERK1/2, Akt/mTOR, and Jak/STAT pathways by JEV 9 . CW-33A might have a clinical application on interfere post-entry stages during JEV replication.…”
Section: Discussionsupporting
confidence: 89%
“…CW-33 had no effect on the infectivity of virus particles and early entry into cells, but showed a significant inhibition on the late stage of JEV replication cycle 9 . Intracellular infectious virus assay demonstrated that CW-33A at 10 μM has a higher decrease in the intracellular production of JEV infectious particles than CW-33 24 or 48 hpi (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations